2015
DOI: 10.1104/pp.15.00403
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Glycosylation in Tea Plants: Sequential Glycosylations for the Biosynthesis of Aroma β-Primeverosides Are Catalyzed by Two Camellia sinensis Glycosyltransferases

Abstract: Tea plants (Camellia sinensis) store volatile organic compounds (VOCs; monoterpene, aromatic, and aliphatic alcohols) in the leaves in the form of water-soluble diglycosides, primarily as b-primeverosides (6-O-b-D-xylopyranosyl-b-D-glucopyranosides). These VOCs play a critical role in plant defenses and tea aroma quality, yet little is known about their biosynthesis and physiological roles in planta. Here, we identified two UDP-glycosyltransferases (UGTs) from C. sinensis, UGT85K11 (CsGT1) and UGT94P1 (CsGT2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
134
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 58 publications
3
134
0
Order By: Relevance
“…The catalytic efficiency of CsUGT85A53‐1 for (Z)‐3‐hexenol ( k cat / K M of 18,499 M −1 s −1 ) is 1.2‐ and 2‐fold higher than that of CsUGT85A53‐2 and CsUGT85A53‐3, respectively (Table ). The kinetics of UGT85K11 for (Z)‐3‐hexenol was further studied (Ohgami et al, ). The apparent K M values of UGT85K11 for (Z)‐3‐hexenol was 40.66 μM (Table S6), which was 2.1‐, 1.5‐, and 1.6‐fold higher than that of CsUGT85A53‐1, CsUGT85A53‐2, and CsUGT85A53‐3 (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The catalytic efficiency of CsUGT85A53‐1 for (Z)‐3‐hexenol ( k cat / K M of 18,499 M −1 s −1 ) is 1.2‐ and 2‐fold higher than that of CsUGT85A53‐2 and CsUGT85A53‐3, respectively (Table ). The kinetics of UGT85K11 for (Z)‐3‐hexenol was further studied (Ohgami et al, ). The apparent K M values of UGT85K11 for (Z)‐3‐hexenol was 40.66 μM (Table S6), which was 2.1‐, 1.5‐, and 1.6‐fold higher than that of CsUGT85A53‐1, CsUGT85A53‐2, and CsUGT85A53‐3 (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the biosynthesis of flavour glycosides, genes for some UGTs have been isolated and identified, recently. Although the phylogenetic analysis can provide information that is able to partially predict the biochemical activities of plant UGTs, some of the enzymes, which were classified in the same cluster, can exhibited different functionalities (Figure ; Ono et al, ; Yauk et al, ; Ohgami et al, ; Song, Hong, et al, ). In our study, the UGT85 family member CsUGT85A53 preferentially glucosylated (Z)‐3‐hexenol, nerol, and other aromatic alcohols (Figure ), whereas AdGT4 from Actinidia deliciosa (Yauk et al, ) and VvGT14 from Vitis vinifera (Bönisch et al, ) showed a similar broad substrate tolerance but with a preference for geraniol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence has been derived from the elucidation of crystal structure, and site-directed mutagenesis studies 15, 4345 .…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the underlying catalytic and regulatory mechanisms and their physiological roles would be of great biotechnological importance for the synthesis of bioactive secondary metabolites in vitro and for the metabolic engineering of crops with important agronomic traits through efficient breeding strategies Kristensen et al, 2005;Weis et al, 2008). Although the ubiquitous GT family has been intensively studied for many years (Gachon et al, 2005) and enzymes involved in the glucosylation of plant products such as anthocyanidins, flavonoids, terpenes, alcohols (Cheng et al, 1994;Almeida et al, 2007;Griesser et al, 2008aGriesser et al, , 2008bBönisch et al, 2014aBönisch et al, , 2014bOhgami et al, 2015), and plant hormones have been functionally characterized, little is actually known about the glucosylation of strawberry aroma chemicals.…”
mentioning
confidence: 99%